Researcher Perspectives on Ethical Considerations in Adaptive Deep Brain Stimulation Trials - Muñoz, Katrina A.; Kostick, Kristin; Sanchez, Clarissa; Kalwani, Lavina; Torgerson, Laura; Hsu, Rebecca; Sierra-Mercado, Demetrio; Robinson, Jill O.; Outram, Simon; Koenig, Barbara A.; Pereira, Stacey; McGuire, Amy; et al. (Frontiers in Human Neuroscience, 2020)
Interest and investment in closed-loop or adaptive deep brain stimulation (aDBS) systems have quickly expanded due to this neurotechnology’s potential to more safely and effectively treat refractory movement and psychiatric disorders compared to conventional DBS. A large neuroethics literature outlines potential ethical concerns about conventional DBS and aDBS systems. Few studies, however, have examined stakeholder perspectives about ethical issues in aDBS research and other next-generation DBS devices. To help fill this gap, we conducted semi-structured interviews with researchers involved in aDBS trials (n=23) to gain insight into the most pressing ethical questions in aDBS research and any concerns about specific features of aDBS devices, including devices’ ability to measure brain activity, automatically adjust stimulation, and store neural data. Using thematic content analysis, we identified 8 central themes in researcher responses. The need to measure and store neural data for aDBS raised concerns among researchers about data privacy and security issues (noted by 91% of researchers), including the avoidance of unintended or unwanted third-party access to data. Researchers reflected on the risks and safety (83%) of aDBS due to the experimental nature of automatically modulating then observing stimulation effects outside a controlled clinical setting and in relation to need for surgical battery changes. Researchers also stressed the importance of ensuring informed consent and adequate patient understanding (74%). Concerns related to automaticity and device programming (65%) were discussed, including current uncertainties about biomarker validity. Additionally, researchers discussed the potential impacts of automatic stimulation on patients’ autonomy and control over stimulation (57%). Lastly, researchers discussed concerns related to patient selection (defining criteria for candidacy) (39%), challenges of ensuring post-trial access to care and device maintenance (39%), and potential effects on personality and identity (30%). To help address researcher concerns, we discuss the need to minimize cybersecurity vulnerabilities, advance biomarker validity, promote the balance of device control between patients and clinicians, and enhance ongoing informed consent. The findings from this study will help inform policies that will maximize the benefits and minimize potential harms of aDBS and other next-generation DBS devices.